Hyperphosphatemic tumoral calcinosis: a rare differential of periarticular swelling - Nanjareddy, Sunil; Paidipatti, Rajashree; Shivalingappa, Vishwanath Muttagaduru; Jagadeesh, Nuthan (International Journal of Research in Medical Sciences, 2020)
Tumour calcinosis is a rare clinical and histopathological syndrome characterised by deposition of calcium deposits in different periarticular soft tissue regions of the body. It mainly manifest in childhood/ adolescence as a painless, firm to hard tumour like mass around the joints. Most common regions involved: Shoulder, elbow and hip. An 18 year old male patient presented to the opd with a history of pain and swelling over his left hip since 2 months. On examination, there was a diffuse tender swelling over the left greater trochanter, skin over the swelling was normal with no discharge, no dilated/ engorged veins. Range of motion of left hip was normal, no limb length discrepancies. X-ray: Showed a well define calcified mass over the greater trochanter with no osseous involvement. MRI revealed an encapsulated hypointense mass present posterior to the greater trochanter, mostly in the muscular plane. Lab findings revealed mild hyperphosphetemia. An aspirate from the swelling showed casseousmaterial. En mass removal was done and sent for biopsy. Biopsy showed features suggestive of tumoral calcinosis. Tumoral calcinosis is a distinct clinico-radiopathological entity characterised by soft tissue periarticular calcinosis which mimics a true neoplasm, associated with elevated levels of serum phosphate. It is an extremely rare condition which is seen in the adolescence and requires more studies regarding the surgical and medical management of the same.